Kepemimpinan Pendidikan dalam Perspektif Islam : Sebuah Kajian Teoritis - Diana Suci Wulandari; Kurnia Wahyuni; Syafaatul Habib (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Leadership is one of the key factors determining whether an organization will achieve victory or experience failure, achieve success or experience setbacks, and be accepted or rejected by the surrounding environment.. The purpose of this study is to examine leadership in the world of education in more depth, especially from the perspective of Islamic teachings. This study is included in the category of qualitative research with a literature review approach. Data collection was carried out through tracing and analyzing relevant literature, such as books and scientific articles, which were then combined to produce findings. The research findings reveal that leadership in Islamic education is based on obedience to Allah SWT and the importance of building harmonious social interactions. The three main principles of Islamic leadership are Amanah (responsibility and trustworthiness), Adil (upholding justice in all aspects of life), and Musyawarah (respecting points of view and building joint decisions). These principles require educational leaders to set a good example by managing resources with integrity, treating all parties fairly, and prioritizing collaborative decision-making.